Observation on the Effects of Intraosseous Access on Inflammatory Mediators, Hematopoietic Cell Function, and Coagulation-Metabolic Disturbances in Emergency Traumatic Hemorrhagic Shock Patients: Intraosseous Access in Emergency Traumatic Hemorrhagic Shock - Deng, Gaorong; Jiang, Lang; Miao, Xin; Dong, Yuying; Gao, Xiang; Li, Zongfang (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the impact of intraosseous (IO) access on inflammatory mediators, hematopoietic cell function, and coagulation-metabolic disturbances in patients presenting with emergency traumatic hemorrhagic shock (THS), thereby providing clinical evidence to refine IO resuscitation protocols in emergency settings. Methods: We conducted a randomized controlled trial involving 84 THS patients admitted between February 2024 and February 2025. Participants were allocated equally into two groups: the IO group (n=42), where vascular access was established via humeral or proximal tibial puncture, and the intravenous (IV) group (n=42), where conventional peripheral or central venous access was prioritized. Serial measurements were performed at baseline (T0), 24 hours (T1), and 72 hours (T2) post-intervention to assess: (1) inflammatory mediators (IL-1β, IL-6, IL-10, HMGB1, MDA); (2) hematopoietic parameters (CD34+ cell proportion, CFU-GM/BFU-E colony formation, CXCL12, EPO, and TPO); (3) coagulation profiles (PT, APTT, and D-dimer); and (4) tissue perfusion indicators (blood lactate and lactate clearance rate). Comparative analyses were conducted both between groups and across different time points. Results: The IO group demonstrated significantly elevated levels of IL-1β, HMGB1, and MDA at T1 and T2 compared to the IV group (P<0.05), coupled with reduced IL-10 expression (P<0.05), indicating exacerbated inflammatory imbalance and oxidative stress. Hematopoietic evaluation revealed progressive declines in CD34+ cell populations, CFU-GM/BFU-E colony formation, and CXCL12 concentration in the IO group at T1 and T2 (P<0.05), despite modest compensatory increases in EPO and TPO that remained inferior to the IV group (P<0.05). Coagulation studies showed prolonged PT/APTT (P<0.01) and higher D-dimer levels (P<0.05) in the IO group, along with worse blood lactate levels and lactate clearance rates compared to the IV group (P<0.05), suggesting increased tissue hypoxia and coagulopathy risk. Conclusion: While IO access enables rapid vascular access for resuscitation and reduces critical intervention time, our findings demonstrate that it may inadvertently aggravate systemic inflammatory dysregulation, impair hematopoietic function, and worsen coagulation-metabolic disturbances through mechanisms such as mechanical stimulation, hypothermic fluid infusion, and oxidative stress.